2D-wavelet wavenumber filtering for structural damage detection using full steady-state wavefield laser scanning. (December 2020) - Jeon, Jun Young; Kim, Duhwan; Park, Gyuhae; Flynn, Eric; Kang, To; Han, Soonwoo
Abstract: This paper presents the use of wavelet-based wavenumber filtering that can be used for damage detection with full steady-state wavefield laser scanning. A piezoelectric transducer provides a single-frequency continuous excitation while a scanning laser doppler vibrometer (SLDV) conducts the full steady-state wavefield measurement. To detect damage, a 2D wavelet transform with various scale components is applied to track any changes in wavenumber and a mapping process based on local wavenumber filtering is carried out. To demonstrate the performance of the proposed technique, several experiments are conducted on composite and aluminum structures, which contain various types of hidden damage, including Teflon inserts and machined thinning. The results demonstrate that this technique performs better than Fourier based wavenumber techniques in terms of damage detection and visualization capability for smaller size defects in a structure. In addition, by providing additional signal processing techniques along with the existing techniques, the proposed method aims to provide rich opportunities to selectively choose the damage detection algorithms for various types of structures and defects, thereby enhancing the damage detection capability of steady-state ultrasonic imaging techniques.